Evolution of strawberry water consumption in soilless culture - Wamser, Anderson Fernando (2022)
The objective of the present work was to evaluate the evolution of the water consumption of the strawberry cv. Albion in the first cycle cultivated in three commercial substrates. The experiment was carried out in Caçador, SC, in a protected environment. The treatments consisted of three commercial substrates with four replications. The daily water consumption of strawberry plants was evaluated by subtracting the daily volume of nutrient solution applied and the daily volume of nutrient solution drained. The water use efficiency was obtained from the relationship between fruit production and total water consumption during the crop cycle. The highest total water consumption was obtained with two substrates tested, with average consumption, during full fruit harvest, of 267.7 and 259.6mL plant-1 day-1. The daily water consumption during the harvest period is not constant, due to the inconsistency of the climatic conditions, typical of the region of Caçador. This fact makes it difficult to use fixed irrigation frequency and times, often resulting in excessive or deficient irrigation.